2022
DOI: 10.3390/nano12091539
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Aluminum-Doped Zinc Oxide, Gallium-Doped Zinc Oxide and Indium-Doped Tin Oxide Thin Films Deposited by Radio Frequency Magnetron Sputtering

Abstract: A timely replacement of the rather expensive indium-doped tin oxide with aluminum-doped zinc oxide is hindered by the poor uniformity of electronic properties when deposited by magnetron sputtering. Recent results demonstrated the ability to improve the uniformity and to decrease the resistivity of aluminum-doped zinc oxide thin films by decreasing the energy of the oxygen-negative ions assisting in thin film growth by using a tuning electrode. In this context, a comparative study was designed to elucidate if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 66 publications
0
7
1
Order By: Relevance
“…A certain positioning of the large plate accommodating the TE was used as a shutter during the time needed for the small adjustments of the deposition parameters. 34 All samples were deposited at a 30 W RF power for 30 min. There was no intentional heating of the substrate except for the mild effect of plasma exposure (below 50 1C).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A certain positioning of the large plate accommodating the TE was used as a shutter during the time needed for the small adjustments of the deposition parameters. 34 All samples were deposited at a 30 W RF power for 30 min. There was no intentional heating of the substrate except for the mild effect of plasma exposure (below 50 1C).…”
Section: Methodsmentioning
confidence: 99%
“…[33,34] Very recently it was demonstrated that gallium doped zinc oxide and ITO exhibit the same dependence of the selfbias with pressure as reported for AZO, however, only AZO exhibited the most noticeable correlation of the optoelectronic properties with the erosion track. [35] The optoelectronic and analytical properties of AZO thin films by sputtering have been intensively studied including X-ray photoelectron spectroscopy (XPS), [36][37][38][39] , X-ray diffraction (XRD) [36,[39][40][41][42] and Raman [37,40] for various parameters (pressure [43][44][45] , power [46][47][48] , target to substrate distance [32,49] , substrate material [50] , oxygen gas fraction [51,52] , substrate temperature [39] , plasma excitation mode [18,53,54] , annealing temperature, [55,56] target erosion [16] , Al doping fraction [57] ). However, so far, no conclusive correlation has been reported between the role of negative oxygen ions and the physical and chemical properties of AZO thin films as to be able to obtain resistivities below 10 -3 cm for a deposited area comparable with that of the target.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aluminum (abundant) or gallium (with a supply potential 10 times higher than indium) are the most widespread materials used in this case. Aluminum (AZO)- and gallium (GZO)-doped zinc oxides are the most promising alternatives to ITO, demonstrating electric conductivities up to 1200 S cm –1 and visible transparencies of around 90%. GZO has started to be preferred lately because of stability issues encountered in the case of AZO, a result of the differences among the ionic radius (Ga 3+ : 0.47 Å; Al 3+ : 0.39 Å; and Zn 2+ : 0.60 Å) as well as the high probability of inactive Al 2 O 3 phase formation. , ZnO-based materials are deposited using basically all known synthesis methods, as many of its applications require polycrystalline films. A special approach is required if a high degree of crystalline quality or purity is envisaged as in the case of advanced optoelectronic devices .…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the case of PVD synthesis, the scientific community has lately been focusing on the detrimental role of the oxygen ions on the uniformity of deposited films. 11,24,25 In the case of ALD synthesis, the latest efforts are oriented toward the understanding of the influence of the dopant/Zn ratio on the growth mode and optoelectronic properties. 26 In the context of 5G deployment as the backbone of trillions of Internet of Things (IoT) devices, innovative designs of antennas represent a major challenge in terms of efficiency in small volume but also as an object that must integrate into their environment in a harmonious way.…”
Section: ■ Introductionmentioning
confidence: 99%